Spatial and temporal variations of water quality and trophic status in Bukit Merah Reservoir, Perak - Mohd Shafiq Zakeyuddin,; Amir Shah Ruddin Md Sah,; Mohd Syaiful Mohammad,; Nurul Fazlinda Mohd Fadzil,; Zarul Hazrin Hashim,; Wan Maznah Wan Omar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
A study of spatial and temporal variations on water quality and trophic status was conducted twice a month from December 2012 to January 2014 in four sampling stations at Bukit Merah Reservoir (BMR). The concentration of dissolved oxygen (DO), water temperature, conductivity, total dissolved solids (TDS), total phosphorous (TP), PO4-, NO2-, NO3-, NH4+ and net primary productivity had significant differences temporally (p<0.05) except for pH, total suspended solids (TSS) and chlorophyll-a. Based on correlation analysis, the amount of rainfall and rain days has negatively correlated with secchi depth and chlorophyll-a (p<0.01). The water level has significantly decreased the value of the temperature, pH, conductivity, TP and NO2- but it has positive correlation with NO3- and NH4+. Discharged from Sungai Kurau increased the value of conductivity, TSS, TP and NO2- as a result from runoff and erosion, thus decreasing the secchi depth values, NO3- and NH4+. The water quality of BMR is classified in Class II and TSI indicates that the BMR has an intermediate level of productivity (mesotrophic) and meets the objective of this reservoir which was to provide water for paddy irrigation.